The Concept of Ethics and Moral Education Based on Katoba Local Culture in the Overseas Muna Community in Kendari City - Musafar Musafar; Hadirman Hadirman; Ardianto Ardianto; Arhanuddin Salim (Institut Agama Islam Negeri (IAIN) Manado, 2023)
Katoba local culture is a tradition owned by the Muna ethnicity, both living in Muna and overseas. Katoba local culture is carried out by the overseas Muna community in Kendari City to strengthen children's Islam and provide ethical and moral education to children aged 7–11 years, both boys and girls. The purpose of this study is to describe the concept of ethics and moral education based on local katoba culture in the overseas Muna community in Kendari City. The method used in this study is a phenomenological approach. The analysis uses a cultural approach. The results showed that the local culture of katoba in the overseas Muna community in Kendari City carried out this tradition as a means of shaping the ethical and moral education of a child. Children are prepared to become individuals who have religious understanding, ethics, and good morals in the midst of society.